Fault Extension Characteristics of the Middle Section of Shanxi Graben System and the Seismogenic Environments of the Hongdong and Linfen Earthquakes - Xingbing Xie; Yan Zhan; Lei Zhou; Simeng Peng (Remote Sensing, 2023)
The Shanxi Graben System exhibits high seismic activity and significant destructive potential. Previous studies in this region have primarily focused on geological methods such as seismology, geological surveys, and trench excavations, with limited research in the field of geophysics. In this study, we collected two magnetotelluric profiles crossing the central segment of the Shanxi Graben System, including the fault system and the Hongdong–Linfen seismic zone. Through qualitative analysis and inversion calculations, we constructed a three-dimensional electrical model of the study area. The seismogenic environment was studied by integrating the deformation field, recent seismic geological data, and geophysical survey results of the study area and its surroundings. The Luoyunshan Piedmont Fault and the Huoshan Piedmont Fault are likely two main faults in the central segment of the Shanxi Graben System. These faults span the entire crustal scale and serve as basement faults separating the Ordos Block and the Taihangshan Block. They exhibit patterns of activity. The western side of the Shanxi Graben System, represented by the Ordos Block, exhibits a stable tectonic environment, while the eastern side, represented by the Taihangshan Block, experiences severe lithospheric destruction and thinning. The results of the magnetotelluric (MT) survey support the 1303 Hongdong earthquake as an event that occurred on the Huoshan Piedmont Fault and provide geophysical evidence for the possible dominance of the Luoyunshan Piedmont Fault in the 1695 Linfen earthquake. Multiple factors controlled the seismogenic environments of these two earthquakes. The continuous upwelling of asthenospheric material in the lower-middle crust on the eastern side of the Linfen Basin possibly leads to the regional extension of the North China Block. This, in turn, triggers inclined sliding along the Huoshan Piedmont Fault and the Luoyunshan Piedmont Fault, which may be the main controlling factors for major earthquakes in the region.